Characterization of the motion of booster-seated children during simulated in-vehicle precrash maneuvers. (25th November 2019) - Graci, Valentina; Douglas, Ethan; Seacrist, Thomas; Kerrigan, Jason; Mansfield, Julie; Bolte, John; Sherony, Rini; Hallman, Jason; Arbogast, Kristy B.
Abstract: Objective: Precrash occupant motion may affect head and trunk position and restraint performance in a subsequent crash, particularly for young children. Others have studied seat belt–restrained adult drivers and adult and adolescent passengers in precrash maneuvers. For younger children, optimal restraint includes a belt-positioning booster seat, which in precrash maneuvers may contribute in unique ways to the overall body motion. Therefore, the objective of this study was to quantify booster-seated child occupant kinematic, kinetic, and muscle responses during precrash maneuvers and characterize booster movement with respect to the overall occupant kinematics. Methods: Vehicle maneuver tests were conducted with a recent model year sedan at the Transportation Research Center Inc. (TRC, Marysville, Ohio). Three precrash vehicle maneuvers were simulated: Automated and manual emergency braking (AEB and MEB) and oscillatory swerving or slalom (SLA). Each maneuver was repeated twice for each participant. Seven 6- to 8-year-old booster-seated children participated in the study and all subjects were seated in the right rear seat. Vehicle dynamics (i.e., motion, position, and orientation) were measured with an inertial and Global Positioning System navigation system (Oxford RT 3003). Kinematic data from human volunteers were collected with an 8-camera 3D motion capture system (Optitrack Prime 13 200 Hz, NaturalPoint, Inc.). Photoreflective markers were placed on participants' head and trunk. Electromyography (EMG; Trigno EMG Wireless Delsys, Inc., 2, 000 Hz) sensors were placed on bilateral muscles predicted to be most likely involved in bracing behaviors. Results: Children demonstrated greater head and trunk velocity in MEB (head 123.7 ± 13.1 cm/s, trunk 77.6 ± 14.1 cm/s) compared to AEB (head 45.31 ± 11.5 cm/s, trunk 27.1 ± 5.5 cm/s; P < .001). Participants also showed greater head motion in MEB (18.9 ± 1.4 cm) vs. AEB (15.1 ± 4.8 cm) but the differences were not statistically significant ( P < .1). Overall, the booster seats themselves did not move substantially (<3 cm) in the braking maneuvers. During the SLA, however, the booster seat moved laterally up to 5 cm in several subjects, contributing substantially to peak trunk (6.5–14.0 cm) and head (9.9–21.4 cm) excursion during the maneuver. Booster-seated children also exhibited a greater activation of biceps and deltoid muscles and abdominal and middle trapezii muscles than the sternocleidomastoids during these maneuvers. Conclusions: The quantification of booster seat motion and neuromuscular control and the relationship between kinematics and muscle activation in booster-seated children in precrash maneuvers provides important data on the transition between the precrash and crash phases for this young age group and may help identify opportunities for interventions that integrate active and passive safety.